Extrarenal Wilms Tumor Mimicking Funicular Hydrocele - Mijovic, Tanja; Rašić, Petar; Miličković, Maja; Đuričić, Slaviša; Savic, Djordje; Djokić, Dragomir; Stajević, Mila (Medical Research, 2024)
Introduction/Objective: Extrarenal Wilms’ tumor (ERWT) comprises 0.5% to 1% of all nephroblastoma cases. The most common locations of ERWT are the retroperitoneum, inguinal, lumbosacral and pelvic region, female genital organs, mediastinum and chest wall, spermatic cord and paratesticular region. ERWT most likely originates from the ectopic nephrogenic rest that undergoes a malignant transformation. The exclusion of primary renal tumor is necessary to establish the diagnosis of ERWT. Patient Review: A 15-month-old male was operated on because of a left-sided inguinal mass that clinically resembled a funicular hydrocele. The surgical exploration of the inguinal canal revealed a solid tumor located in the area of the external inguinal ring, measuring around 2cm in diameter, with no ingvinal hernia present. Complete surgical resection of the mass was performed. The histological structure of the tumor corresponded to non-anaplastic nephroblastroma (Wilms tumor), mixed type. After abdominal CT scan primary renal tumor was excluded and the diagnosis of ERWT was made. Because of microscopic tumor rests on the resection margin, the patient was treated according to the high-risk SIOP Wilms tumor protocol. The patient made a full recovery. During the 10-year follow-up, the boy has remained disease free. Conclusion: ERWT is mostly diagnosed after surgical removal of the specimen. The clinical resemblance of the ERWT located in the inguinal region to common benign inguinal conditions in children may lead to the omission of detailed preoperative work-up. Most children with ERWT in the inguinal region have an excellent prognosis, although most of them require adjuvant chemotherapy and/or radiotherapy after surgery.